Coinfections and Phenotypic Antimicrobial Resistance in Actinobacillus pleuropneumoniae Strains Isolated From Diseased Swine in North Western Germany—Temporal Patterns in Samples From Routine Laboratory Practice From 2006 to 2020 - Hennig-Pauka, Isabel; Hartmann, Maria; Merkel, Jörg; Kreienbrock, Lothar (Frontiers in Veterinary Science, 2022)
Actinobacillus pleuropneumoniae (APP) is one major bacterial porcine respiratory tract pathogen causing diseases outbreaks worldwide, although effective commercial vaccines are available. Due to frequent failure of this preventive measure, treatment with antimicrobials is indispensable to prevent animal losses within an outbreak situation. To preserve effectivity of antimicrobial substances to fight APP should therefore be the primary aim of any interventions. In this study, the temporal development of antimicrobial resistance in APP was analyzed retrospectively in the time period 2006-2020 from a routine diagnostic data base. In parallel, frequent coinfections were evaluated to identify most important biotic cofactors as important triggers for disease outbreaks in endemically infected herds. The proportion of APP serotype 2 decreased over time but was isolated most often from diseased swine (57% in 2020). In approximately 1% of the cases APP was isolated from body sites outside the respiratory tract as brain and joints. Lowest frequencies of resistant isolates were found for cephalothin and ceftiofur (0.18%), florfenicol (0.24%), tilmicosin (2.4%), tiamulin (2.4%), enrofloxacin (2.7%) and spectinomycin (3.6%), while the highest frequencies of resistant isolates were found for gentamycin (30.9%), penicillin (51.5%) and tetracyclin (78.2%). For enrofloxacin, tiamulin, tilmicosin and tetracyclin significantly lower frequencies of resistant isolates were found in the time period 2015-2020 compared to 2006-2014, while gentamicin resistant isolates increased. In summary, there is only a low risk of treatment failure due to resistant isolates. In maximum up to six co-infecting pathogens were identified in pigs positive for APP. Most often pigs were coinfected with Porcine Circovirus 2 (56%), Streptococcus suis (24.8%) or the Porcine Reproductive and Respiratory Syndrome Virus (23.3%). Potential synergistic effects between these pathogens published from experimental findings can be hypothesized by this field data as well. To prevent APP disease outbreaks in endemically infected herds more efficiently in the future, next to environmental trigger factors preventive measures must also address the co-infecting agents.